STRATEGI KEBIJAKAN PEMANTAPAN KAWASAN KESATUAN PENGELOLAAN HUTAN LINDUNG (KPHL) MODEL KAPUAS KALIMANTAN TENGAH - Jovan Sofyan; Mahrus Aryadi; Mufidah Asy'ari (Jurnal Hutan Tropis, 2016)
The purpose of this study is to identify the policies and processes related to the consolidation of forest land in the area KPHL Model Kapuas, and formulate strategies stabilization policy in the area of forest area KPHL Model Kapuas. Identification Policies and Processes Forest Area Consolidation is done by collecting data regulations regarding clarification of the forest area. Forest Area Stabilization Policy strategy using SWOT analysis to reveal the internal factors and external factors that are considered important in achieving the goal, which is to identify the strengths, weaknesses, opportunities and threats. The results of the identification of policies and clarification of forest areas shows that the internal forces KPHL Model Kapuas is their legislation, activities boundaries of land has been gathering bracelet and the strong position of KPHL in RTRWP, while the chances of the external is the absence of government support through the process of accelerating the inauguration of forest area , The model is a progressive strategy employed is to speed up the gazetting of forest areas through mapping and determination of the results of the boundary area KPHL Model Kapuas.Tujuan penelitian ini adalah mengidentifikasi kebijakan dan proses yang berkaitan dengan pemantapan kawasan hutan di areal KPHL Model Kapuas, dan merumuskan strategi kebijakan pemantapan kawasan hutan di areal KPHL Model Kapuas.  Identifikasi Kebijakan dan Proses Pemantapan Kawasan Hutan dilakukan dengan mengumpulkan data-data peraturan yang berlaku terkait proses pemantapan kawasan hutan. Strategi Kebijakan Pemantapan Kawasan Hutan menggunakan analisis SWOT dengan mengungkapkan faktor internal dan faktor eksternal yang dianggap penting dalam mencapai tujuan, yaitu dengan mengidentifikasi kekuatan, kelemahan, kesempatan dan ancaman. Hasil identifikasi kebijakan dan proses pemantapan kawasan hutan menunjukan bahwa kekuatan internal KPHL Model Kapuas adalah adanya peraturan perundang-undangan, kegiatan tata batas kawasan hutan telah temu gelang serta kuatnya posisi KPHL dalam RTRWP, sedangkan peluang eksternalnya adalah adanya dukungan pemerintah melalui proses percepatan pengukuhan kawasan hutan. Model strategi yang ditempuh adalah progresif yaitu dengan mempercepat proses pengukuhan kawasan hutan melalui pemetaan dan penetapan hasil tata batas areal KPHL Model Kapuas.